Desplazamientos de la iguana verde, Iguana iguana (Squamata: Iguanidae) durante la estación seca en La Palma, Veracruz, México - E. Morales Mavil, Jorge (2007)
The green iguana (Iguana iguana) is said to be primarily sedentary, although the females travel long distances to nest. Displacement patterns must be known to help predict the effects of environmental disturbance on iguanas’ survival. We studied nesting season (February-July) move-ments in La Palma, Los Tuxtlas, Veracruz, Mexico (18°33’ N, 95°03’ W). Individual movements and activity were monitored by radio tracking. The transmitters were implanted surgically in eight adult iguanas (four males and four females). Snout vent length (SVL) was used to determine the relationship between size of the body and size of home range. To estimate the size of home range, three or more points were used. Minimum convex polygons estimates of home range were calculated with McPAAL. The iguanas were radio-located between 23 and 30 occasions, mainly in trees (56 % between 3-9 m); only 4 % were localized under a height of 3 m (forest floor). The occupation area mean was larger for males (9 158.06±3 025.3m2 vs. 6 591.24±4 001.1 m2) although the differences were not significant (t= 0.51, p>0.05). SVL was correlated with home range (r= 0.76; gl= 7; p<0.05). Breeding males defended their home range vigorously against other adult males. We observed one separate male home range and large portions of overlap between the sexes. The home range generally formed a conglomerate of polygons and only two had linear shapes along the river: apparently iguanas use the riparian vegetation for foraging. The females display two strategies for nesting: 1) moving to the sandy area near the sea or, 2) laying eggs near the river, in loam. Iguanas responded to habitat fragmentation and reduction by modifying their nesting strategy.